Поверхневi бiлки-адгезини стафiлококiв та їх амiнокислотнi послiдовностi - Олешко, Г.М.; Любченко, Г.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The Staphylococcus aureus infection remains a problem of today’s time. Adhesion of the cells of bacteria to fabrics of the owner is an initial critical step in the pathogenic process. On the literary data, the important role in adhesion of S. aureus is played by surface adherence proteins. The purpose of our work was to perform the analysis of aminoacides of the surface adherence proteins received by us from strain Wood-46(2351) and to compare the obtained data with the literary ones. As a result of the analysis, we note two different pairs: methionineysteine and glutamine-asparagine. These amino acids can influence the adhesion properties of S. aureus and can be a stimulus for the formation of the immune answer.